CROSS-SUBJECT SYNERGY AND INNOVATIVE PRACTICE OF INTANGIBLE CULTURAL HERITAGE EDUCATION IN THE DIGITAL AGE: A STUDY BASED ON THE INHERITANCE OF YI ETHNIC CLOTHING CULTURE IN LIANGSHAN - Zheng , Yuwei; Zainuddin, Nasaie (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The rapid development of digital technology has brought new opportunities and challenges to the education of Intangible Cultural Heritage (ICH), and insufficient collaboration among multiple stakeholders is a core bottleneck hindering the large-scale, sustainable development of ICH education. This study takes the inheritance of Yi ethnic costume culture in Liangshan as a case, drawing on theories of collaborative governance, cultural adaptation, and digital communication, and adopting a mixed-method research approach to explore the cross-stakeholder collaborative mechanism and the innovative path of ICH education in the digital age. The research revealed that the effective implementation of ICH education requires the construction of a four-in-one collaborative framework of "government - school - community - enterprise." It is also discovered that digital technology plays a key role in resource integration, scene expansion, and communication empowerment. Through innovative practices such as virtual workshops, online learning communities, and short video teaching, the collaborative education model has achieved multiple effects. This includes expanding educational coverage, increasing youth participation, and enhancing cultural communication. In addition, the "digital empowerment - cross-stakeholder collaboration" framework for ICH education constructed by this study provides an empirical solution to the problems of resource dispersion, an inheritance gap, and innovation deficiency in the education of ICH among ethnic minorities, and has important reference value for promoting the modern transformation of ICH education.